Madinat al-Zahra, Spanien. Die Arbeiten des Jahres 2019 - Arnold, Felix (e-Forschungsberichte des DAI, 2020)
Madīnat al-Zahrā’ was founded in 940 AD near Córdoba, Spain as the capital of the Umayyad caliphate. The aim of a five-year project of the German Archaeological Institute and the Junta de Andalucía is the investigation of the socalled Plaza de Armas, the central public square of the city. This season the eastern limit of the plaza was studied, providing new insight into the development of the plaza. Originally two separate building complexes stood across from each other, the palace of the caliph to the west and a second palace to the east, possibly inhabited by the crown prince. In a second phase a monumental plaza was constructed between the two existing buildings. Two porticos now faced each other across the plaza. This season a part of the eastern portico was excavated, including the central gate leading to the eastern palace. In 1010 AD the portico and the gate were destroyed by fire. From the destruction debris, elements of the gate were recovered, among them fragments of an arcade that had been located above the gate. Iron fittings of the gate were found, as well as an iron clad shutter of the arcade.